Patient Trend of FDG PET-CT Imaging at NINMAS: Working Experience of First Six Years - Begum, Shamim MF; Siddique, Abu Bakker; Mutsuddy, Pupree; Mandal, Tapati; Akhter, Papia; Kar, Rashmi; Nath, Khokon Kumar (Bangladesh Journal of Nuclear Medicine, 2022)
Abstract not available Bangladesh J. Nuclear Med. 25(1): 36-40, 2022